Edukasi Pemilihan dan Penggunaan Kosmetik yang Aman pada Kalangan Remaja - Armadany, Fery Indradewi; Sartinah, Ari; Mahmudah, Rifa'atul; Sawitri, Feny Eka; Andriani, Kris; Nining, Nining; Rismawati, Rismawati; Putri, Riska Damayanti (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of current beauty trends influences consumer patterns in Indonesia, especially teenagers, thus encouraging the emergence of a new industry with various types of cosmetics that can be freely purchased by the wider community. This socialization was carried out with the aim of educating students to be wiser in choosing safe cosmetics. The method applied was a direct socialization method to students at SMA N 12 Kendari, providing questionnaires to see the increase in understanding after education, direct socialization and socialization carried out using leaflet media. The results obtained showed that the participants' knowledge of how to choose and use everyday cosmetics properly and safely increased. This is reflected in the average pretest value of 66.4 and the average posttest value of 89.3. The test results showed an increase in knowledge about the use of cosmetics of up to ± 22.9%. The conclusion of this activity is that socialization about safe cosmetics is very relevant and can be well received by teenagers and is able to increase teenagers' understanding of cosmetics that are safe to use, so that similar activities can be expanded to other places.